Being the boss - Hill, Linda A. (Harvard Business Review Press, 2019)
You're not alone. As Harvard Business School's Linda Hill and manager and executive Kent Lineback reveal in Being the Boss, becoming an effective manager is a painful, difficult journey. It requires trial and error, endless effort, and slowly acquired personal insight. Many managers never complete the journey and instead just learn how to get by. At worst, they become terrible bosses